Agility in responding to disruptive digital innovation: Case study of an SME. (9th August 2018) - Chan, Calvin M.L.; Teoh, Say Yen; Yeow, Adrian; Pan, Gary
Abstract: Disruptive digital innovation (DDI) often creates hypercompetitive market environment that forces firms to be agile to survive and remain competitive. Whereas most studies have focused on larger firms' effort to be agile, few have looked at how small‐ and medium‐sized enterprises (SMEs) respond to DDI. The study attempts to answer the research question of how SMEs achieve agility to respond to DDI. Drawing on a case study of an innovative SME, our study develops a framework on agility based on the processes of mitigating organizational rigidity, developing innovative capabilities, and balancing the tension of organizational ambidexterity. Specifically, our findings show that for SMEs, mitigating organizational rigidity is enabled by the mechanism of achieving boundary openness while developing innovative capability is enabled by the mechanism of achieving organizational adaptability. At the same time, given the inherent challenges of resource constraints, SMEs also need to balance the tension of organizational ambidexterity.